Women in the workplace the perceived roles of female broadcaster in Iloilo City - Evasco, Mary Margarette Lyn
This study focuses on describing the perceived roles of female broadcasters today. Factors that may affect or influence their perception are: (1) their position in the company, (2) their educational background, and (3) tenure in their job. The purpose of this study is to create awareness about the currents situation of the women working in the broadcast media specifically in the newsroom where majority of the employees are men. Through the use of a survey, the researcher interviewed 18 respondents from all tV and AM radio stations in Iloilo City. The interview was about the experiences of the female broadcasters in their workplaces where there is a so called ?male-dominated reporting.? They were also asked to answer a questionnaire that will give the researcher an idea on how the female broadcasters perceive their importance in the company. The results of the survey showed that majority of female broadcasters perceive their role positively and look at themselves and their presence in the company as something that is as vital as the role of the male broadcasters.